Factors and topics associated with empathic self-disclosure in dignity therapy of cancer patients - Alyssa Crowe; Mary Kate Koch; Susan Bluck; Tithi Amin; Lyndsey Thomas; George Fitchett; Diana J. Wilkie; Carma L. Bylund (Elsevier, 2024)
Objective: During Dignity Therapy a trained provider guides a patient to share their life story and legacy. Providers can demonstrate empathy through empathic self-disclosure (ESD), sharing something substantial and personal about themselves in response to the patient. The current study aims to identify the topics of ESDs and determine whether ESD frequency varied by patient and/or provider characteristics. Methods: Two coders analyzed 203 audio-recorded, transcribed Dignity Therapy sessions of palliative care patients (M = 65.78 years; SD = 7.43 years, 65.69% women) for ESD. Topic modeling characterized themes of ESD and multilevel modeling examined ESD frequency based on several patient and provider characteristics. Results: ESD occurred in 37% of interviews (M = 0.59, SD = 1.21). Topic modeling revealed five main themes: family, memory, school, geographical experiences, and values/beliefs. Multilevel modeling indicated patient-level differences, including greater rates of ESD when patients were men and older. Conclusion: ESD seems to be dependent on the context of the patient rather than individual communication style differences. Providers may use ESD in multiple instances, including when similar and different from patients. Innovation: This study introduces and defines the novel concept of ESD. It is among the first to examine patient-provider communication during Dignity Therapy, and the first to specifically examine self-disclosure.